Peningkatan Kemampuan Pemahaman Peserta Didik pada Mata Pelajaran Matematika Menggunakan Model Project Based Learning - Riyah Riyah; Seruni Seruni (JKPM (Jurnal Kajian Pendidikan Matematika), 2015)
The aim of this research is to describe the increase of students’ comprehension with Project Based Learning (PBL) Model. Sample was taken 25 students. The method of this reaserch is experiment quantitative with purposive sampling. The data analysis used lilifors test to normality test and F test to homoginity test. From the  result of hypothesis used  test at the significant level , ttest 4.42 and ttabel 2.064  with the degrees of freedom (db) = n – 1 = 25 – 1 =  24 is 2.064 get ttest > ttabel = 4.42 > 2.064. It shows that H0 is rejected, so it can be concluded   that there is a significant effect between pretest and posttest. So there is an increasing of students’ comprehension using project based learning model.